To Mix or Specialise? A Coordination Productivity Indicator for English and Welsh farms. (September 2016) - Ang, Frederic; Kerstens, Pieter Jan
Abstract: This paper introduces a nonparametric measure of coordination productivity growth where the subprocesses are explicitly modelled in the production technology. The coordination productivity indicator is decomposed into a coordination technical inefficiency change component and a coordination technical change component. This decomposition allows assessment of reallocation impacts on the different sources of productivity growth. The empirical application focuses on a large panel of English and Welsh farms over the period 2007–2013. The results show that coordination inefficiency significantly increases with the proportion of resources allocated to livestock production in economic and statistical terms. Coordination inefficient farms should generally allocate more land to crop production. Depending on the region, the average coordination productivity growth ranges from −9.7% to 15.9% per year. It is driven by coordination technical change rather than coordination inefficiency change.